2020
DOI: 10.3390/antibiotics9050257
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Bacteriophage and Complex Tannins against Biofilm-Forming Shiga Toxin-Producing Escherichia coli from Canada and South Africa

Abstract: Bacteriophages, natural killers of bacteria, and plant secondary metabolites, such as condensed tannins, are potential agents for the control of foodborne pathogens. The first objective of this study evaluated the efficacy of a bacteriophage SA21RB in reducing pre-formed biofilms on stainless-steel produced by two Shiga toxin-producing Escherichia coli (STEC) strains, one from South Africa and the other from Canada. The second objective examined the anti-bacterial and anti-biofilm activity of condensed tannin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…As far as we know, this is the first report of STEC positivity in animals raised under BPS condition in Chile, detecting positivity in sheep (35%), cattle (25%), duck (15%), goat (10%), hens (10%), and swine (5%), highlighting the importance of BPS in terms of animal and public health. Serotypes reported by this study are commonly detected in animals or animal products ( 66 , 67 ), and linked to animal and human diarrhea ( 68 ) and HUS, under particular conditions ( 69 , 70 ). It is important to highlight that no O157 STEC strains were detected in this study, high morbidity, and mortality serotype linked to animal transmission ( 71 ).…”
Section: Discussionmentioning
confidence: 72%
“…As far as we know, this is the first report of STEC positivity in animals raised under BPS condition in Chile, detecting positivity in sheep (35%), cattle (25%), duck (15%), goat (10%), hens (10%), and swine (5%), highlighting the importance of BPS in terms of animal and public health. Serotypes reported by this study are commonly detected in animals or animal products ( 66 , 67 ), and linked to animal and human diarrhea ( 68 ) and HUS, under particular conditions ( 69 , 70 ). It is important to highlight that no O157 STEC strains were detected in this study, high morbidity, and mortality serotype linked to animal transmission ( 71 ).…”
Section: Discussionmentioning
confidence: 72%
“…However, they found that the addition of magnesium chloride had no effect on phage effectiveness. The results shown in our study further imply that P100 inactivation in apples may be due to factors other than pH, such as the presence of tannins, which have also been linked to antiviral effects [ 57 ]. Further work is needed to determine the factors affecting phage loss on apples in order to select against them.…”
Section: Resultsmentioning
confidence: 55%
“…Hence, the impact on human health and the economic losses have promoted the development of different approaches to control or remove the biofilms. In recent years, bacteriophages were applied as a tool to reduce biofilm formation in various pathogenic bacteria, such as Pseudomonas aeruginosa [ 27 , 28 , 29 , 30 , 31 ], Klebsiella pneumoniae [ 32 ], E. coli [ 33 , 34 , 35 , 36 , 37 ], and Staphylococcus epidermidis [ 38 ]. Thus, bacteriophages were tested in this study to treat biofilms produced by STEC strains.…”
Section: Discussionmentioning
confidence: 99%